Changing for Good : Sustaining School Improvement. - Andris, Melissa Evans (SAGE Publications, 2009)
The most beneficial school improvements are the ones that last. This book offers strategies for sustaining improvement by creating a shared vision, distributing leadership, and celebrating gains.